If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2j + -12 = 2 Reorder the terms: -12 + 2j = 2 Solving -12 + 2j = 2 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 2j = 2 + 12 Combine like terms: -12 + 12 = 0 0 + 2j = 2 + 12 2j = 2 + 12 Combine like terms: 2 + 12 = 14 2j = 14 Divide each side by '2'. j = 7 Simplifying j = 7
| -5.7=1.9+1.9z | | 4n-3=29+8n | | 2x-52=88 | | 8x-11+15x+3x+9=180 | | -5x-4(-x-17)=76 | | y+7=7(x-2) | | -10(b+645)=-490 | | 15-1/2b= | | 4w-60=440 | | 2g-17=1 | | y-6=6(x+6) | | 7xc=-3 | | 8x-1+15x+3x+9=360 | | Z+5=5 | | 5x+7(-x-14)=-88 | | 13x-30=9 | | 10x+3+3x+24=180 | | 24x^2+-12x+-12=0 | | 22/25-7/10 | | 5/20=30/x | | 8x-1+15x+3x+9=90 | | y+4=4(x+7) | | -7y-7=-5(y+5) | | Log(4x+12)=2 | | 72x+56=-84-37x | | 3u-5=10 | | 5/20=3-/x | | 8x-1+15x+3x+9=180 | | 8x-6y=56 | | Q/6--112=125 | | 0=-16x^2+560 | | -9/p-3=3/5 |